Deiksis dalam Percakapan Bahasa Taba pada Masyarakat Desa Walo Pulau Makian Timur - Rafik M Abasa; Taib Abdullah; Kodrat Hi. Karim; Nurul Febriyanti A. Rachma; Muammar Abd. Halil (Universitas Khairun, 2026)
The purpose of the research to be achieved is to describe the form of persona deiksis, time deiksis and place deiksis in Taba language. The method used in this study is a qualitative descriptive method. The data in this study are conversations between fellow Taba speakers that contain deiksis, be it deiksis persona, time and place. The data source used in this study is the people of Walo Village, East Makian Island as speakers of the Taba language itself. The data collection techniques used are, observation, interviews, recording and looking at notes. Based on the data analysis and conclusion, it is known that (1) Persona deixis is divided into three namely first person deixis, second person deixis and third person deixis. The persona deixis are: (a) First person singular deixis: Yak (b) Plural first person deixis: Tit and Am. (c) Singular second person deixis: Au. (d) Plural second person deixis: Meu. (e) Third person singular deixis: I. (f) Plural third person deixis: Si. (2) Time deixis is divided into past time, present time and future time. (a) Past tense deixis: Laimo, Opine, Opaso and Opaso okik opaso. (b) Present tense deixis: Oras ne, Mamadiding ne and Pait ne. And (c) Forms of future time deixis: Moto, Moa and Opolu. (3) Place deixis is divided into deixis forms: An'ne, Addia, Noge.